2018
DOI: 10.1111/1751-7915.13253
|View full text |Cite
|
Sign up to set email alerts
|

Chrysomya megacephala larvae feeding favourably influences manure microbiome, heavy metal stability and greenhouse gas emissions

Abstract: Summary Chrysomya megacephala is a saprophagous fly whose larvae can compost manure and yield biomass and bio‐fertilizer simultaneously. However, there are concerns for the safety of the composting system, that is risk of diseases spread by way of manure pathogens, residue of harmful metals and emission of greenhouse gases. Microbiota analysis and heavy metal speciation by European Communities Bureau of Reference were evaluated in raw, C. megacephala‐composted and natural stacked swine manure to survey pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Iwasa et al [74] observed 66 and 87% reductions in cumulative CH 4 and N 2 O emissions from cattle manure using Neomyia cornicina larvae. Similar results were obtained by Wang et al [182], who found that Chrysomya megacephala larvae can reduce by 58 and 66% of CH 4 and N 2 O emissions, respectively, from swine manure. Moreover, depending on the humidity, H. illucens larvae may reduce by 72.6-99.9% and 99.6-99.9% of CH 4 and N 2 O, respectively, compared to conventional composting [27].…”
Section: Greenhouse Gases Emissions From the Bioconversion Processsupporting
confidence: 90%
See 1 more Smart Citation
“…Iwasa et al [74] observed 66 and 87% reductions in cumulative CH 4 and N 2 O emissions from cattle manure using Neomyia cornicina larvae. Similar results were obtained by Wang et al [182], who found that Chrysomya megacephala larvae can reduce by 58 and 66% of CH 4 and N 2 O emissions, respectively, from swine manure. Moreover, depending on the humidity, H. illucens larvae may reduce by 72.6-99.9% and 99.6-99.9% of CH 4 and N 2 O, respectively, compared to conventional composting [27].…”
Section: Greenhouse Gases Emissions From the Bioconversion Processsupporting
confidence: 90%
“…Different studies reveal the ability of H. illucens and M. domestica larvae to reduce microorganisms on different substrates [38,87,89,102,124,179,197,198]. In this way, Wang et al [182] associated the reductions of CH 4 and N 2 O emissions from swine manure to the effect of C. megacephala larvae on reducing the abundance of methanogenic bacteria (Methanogens, Methanomassiliicoccaceae, Methanobrevibacter) and increased betaproteobacteria after the bioconversion process.…”
Section: Greenhouse Gases Emissions From the Bioconversion Processmentioning
confidence: 99%
“…(besides Musca spp.) on Ladang UPM farm was due to the behaviour of this species which sought cattle dung as its preferred food source, as well as its breeding site (Wang et al, 2018). Infestation of fly larvae in live animals can cause myiasis, leading to tissue necrosis in cattle (Ferraz et al, 2010), which was not recorded in our study area.…”
Section: Discussionmentioning
confidence: 73%
“…We speculate that this may be related to the presence of more sulfides in the sediments. Pseudomonas plays an important role in processing heavy metals ( Zhang et al, 2017 ; Wang X. et al, 2018 ). These microorganisms also play an important ecological role in our co-occurrence network.…”
Section: Discussionmentioning
confidence: 99%